Short and Long Term Impact on Oral Health Related Quality of Life After Maxillofacial Trauma - Mahat, Arun Kumar; Panta, Niranjan; Shrewastwa, Mukesh Kumar; Puri, Reecha; Basnet, Lila Bahadur (Journal of Nepal Health Research Council, 2023)
Background: Maxillofacial fracture cases require detailed diagnosis, planning and timely restoration of the proper function and aesthetics of the traumatized tissues, as well as appropriate physical, psychological and social rehabilitation to achieve the best possible treatment outcome. Oral health related quality of life allows oral healthcare professionals to evaluate the efficacy of treatment protocols from patients’ perspectives and allows clinician to address and measure the clinically meaningful changes. Methods: The study was carried out in 86 patients with fracture of any one facial bone from September 2020 to March 2022 in Department of Dental Surgery, Nepalgunj Medical College Teaching Hospital, Kohalpur, Nepal. The quality of life was assessed by using Nepali version of Oral Health Impact Profile (OHIP-14) questionnaire, modified to address maxillofacial injury/treatment. Results: A total of 86 patients (male: Female ratio=40:3) were included in the study with mean age of 30.69±11.88 years. Patient with fracture of mandible and midface showed complete recovery on OHIP-14 Scale after 6 months whereas, in patient with panfacial fracture some residual effect in quality of life (0.13±0.50) was seen in two domains psychological discomfort (0.06±0.25) and social disability (0.06±0.25) even after 6 months. Conclusions: Impact of maxillofacial fracture on quality of life is long lasting and huge on patients. Referral to a psychiatrist or psychologist might be beneficial in addition to open reduction and internal fixation of maxillofacial fractures as early as possible to achieve better quality of life in maxillofacial fracture cases. Keywords: Maxillofacial fractures; OHIP-14; quality of life